Deferiprone‐induced agranulocytosis: 20 years of clinical observations - Tricta, Fernando (Am J Hematol, 2016)
Use of the iron chelator deferiprone for treatment of iron overload in thalassemia patients is associated with concerns over agranulocytosis, which requires weekly absolute neutrophil counts (ANC). Here, we analyze all episodes of agranulocytosis (n = 161) and neutropenia (n = 250) during deferiprone use in clinical trials (CT) and postmarketing surveillance programs (PMSP). Rates of agranulocytosis and neutropenia in CT were 1.5% and 5.5%, respectively. Of the agranulocytosis cases, 61% occurred during the first 6 months of therapy and 78% during the first year. These events appeared to be independent of dose, and occurred three times more often in females than males. Their duration was not significantly shortened by use of G‐CSF. No patient with baseline neutropenia (n = 12) developed agranulocytosis during treatment, which raises questions about the validity of prior neutropenia as a contraindication to use. Only 1/7 novel neutropenia cases in CT progressed to agranulocytosis with continued treatment, indicating that neutropenia does not necessarily lead to agranulocytosis. The agranulocytosis fatality rate was 0% in CT and 15/143 (11%) in PMSP. Rechallenge with deferiprone produced agranulocytosis in 75% of patients in whom the event had already occurred, and in 10% with previous neutropenia. Weekly ANC monitoring allows early detection and interruption of therapy, but does not prevent agranulocytosis from occurring. Its relevance appears to decrease after the first year of therapy, when agranulocytosis occurs less often. Based upon analysis of data collected over the past 20 years, it appears that patient education may be the key to minimizing agranulocytosis‐associated risks during deferiprone therapy. Am. J. Hematol. 91:1026–1031, 2016. © 2016 The Authors. American Journal of Hematology Published by Wiley Periodicals, Inc.